2003
DOI: 10.1017/s1092852900018733
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in the Preventive Treatment of Episodic Migraine: A Combined Analysis From Pilot, Double-Blind, Placebo-Controlled Trials

Abstract: The safety and efficacy of medications for preventive treatment of migraine is the subject of current concern and investigation in health care. Two single-center, double-blind, placebo-controlled studies were conducted to evaluate the efficacy and safety of topiramate for migraine prophylaxis. Seventy patients with a diagnosis of migraine were randomly assigned to topiramate-treated and placebo groups. The studies consisted of a 4-week baseline phase, a 6—8 week titration, and 8–12 weeks of maintenance. Topira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 14 publications
2
29
0
1
Order By: Relevance
“…Several randomized, placebo-controlled trials examining topiramate in the treatment of migraine prophylaxis have demonstrated a statistically significant reduction in the frequency of migraine headaches with topiramate compared with placebo (132)(133)(134)(135)(136)(137)(138). Doses have ranged from 50 mg/day to 200 mg/day.…”
Section: Carbamazepinementioning
confidence: 99%
“…Several randomized, placebo-controlled trials examining topiramate in the treatment of migraine prophylaxis have demonstrated a statistically significant reduction in the frequency of migraine headaches with topiramate compared with placebo (132)(133)(134)(135)(136)(137)(138). Doses have ranged from 50 mg/day to 200 mg/day.…”
Section: Carbamazepinementioning
confidence: 99%
“…This study used data on reduction in mean monthly migraine frequency from published clinical trials combined with US drug prices to estimate the monthly costs of preventive therapy with topiramate 200 mg/day, gabapentin, divalproex sodium, and metoprolol, and the number of migraines per month required for the savings in acute medication costs to offset preventive medication costs. The efficacy data for topiramate 200 mg/day were taken from the study of Edwards et al (2003).…”
Section: Economic Evidencementioning
confidence: 99%
“…year, and had a frequency of migraine attacks of at least two per month (Storey et al 2001;Edwards et al 2003), 2-6 per month (Mei et al 2004), or 3-12 per month (Brandes et al 2004;Diener et al 2004;), but no more than 15 migraine days per month (Brandes et al 2004;Diener et al 2004). The frequency of migraines in the population in the RCTs corresponds broadly to the frequency considered an indication for preventive treatment in the US guidelines (Snow et al 2002; see Table 4).…”
Section: Patient Group/populationmentioning
confidence: 99%
“…Many recent studies, even those conducted in children [18], have shown efficacy in migraine prophylaxis, both for migraine without aura and presently also for that with aura [19], and also in other forms of primary headache, yielding good results both in terms of frequency and efficacy at dosages of 100 mg/day [18,[20][21][22][23][24][25][26][27][28][29]. In a study just published, Brandes et al [23] demonstrated that the average monthly headache crisis frequency was reduced significantly, even at the dosage of 100 mg/day of topiramate (p=0.008) as well as at that of 200 mg/day (p<0.001) compared to placebo.…”
Section: Topiramatementioning
confidence: 99%